Book of the dead [compact disc, unabridged] - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series., 2007)
Dr. Kay Scarpetta opens a private forensic pathology practice in Charleston, South Carolina, only to find herself and her colleagues--Pete Marino and her niece, Lucy--confronted by a horrifying series of crimes that may have an underlying link.